Pemberdayaan Masyarakat Berbasis Penguatan Pendidikan Nilai Al Islam - Yani Fitriyani; Oman Hadiana; Asep Usamah; Dodi Ahmad Haerudin; Mustaid (Journal of Innovation and Sustainable Empowerment, 2023)
Community service activities carried out by STKIP Muhammadiyah Kuningan present downstream science and technology through programs directly to the community in Puncak Village, Cigugur District. The purpose of this community service activity is to carry out the Islamic (Islamic Religious Education) field program based on the results of a situation analysis and requests from the community. The method of community service activities uses focus group discussions (FGD) both internally as a Community Service Team (PKM) and with the Puncak Village community. The results of community service activities from the program that have been carried out consist of Islamic boarding school activities with character-building material (akhlaq), reading and writing the Koran. The history of Islamic culture (history of the Prophet Muhammad SAW), guidance on the Mosque Youth Association (IRMAS) with the material studied regarding the organization, learning, and public speaking, the implementation of other programs is counseling on the dangers of drugs for the younger generation, and the tadarus bada program for tarawih prayers in the holy month of Ramadan. Further PKM activities are sought to collaborate with related institutions or agencies to help alleviate/resolve existing problems in the village.